Computational intelligence in information systems : proceedings of the Computational Intelligence in Information Systems Conference (CIIS 2016) - Somnuk Phon-Amnuaisuk; Au, Thien-Wan; Omar, Saiful (Springer, 2017)
This book constitutes the Proceedings of the Computational Intelligence in Information Systems conference (CIIS 2016), held in Brunei, November 18-20, 2016. The CIIS conference provides a platform for researchers to exchange the latest ideas and to present new research advances in general areas related to computational intelligence and its applications. The 26 revised full papers presented in this book have been carefully selected from 62 submissions. They cover a wide range of topics and application areas in computational intelligence and informatics.
Keywords: Computational intelligence -- Congresses.; Artificial intelligence -- Congresses.; Information technology -- Congresses.; elektronické knihy; electronic books